Evaluating the motives of child labourers in the informal economy - Aamar Ilyas; Muhammad Shehryar Shahid; Ramraini Ali Hassan (2020)
Conventionally, the marginalised population was considered to engage in child labour due to poverty, education or lack of other options, but indeed, a few children work voluntarily. However, a growing number of scholars, in recent years, have drawn their attention to the valuable question, “why children are engaged in child labour in the informal economy”. Even though a few studies have explored the motives of informal workers, to our knowledge not a single paper has explored the motives of child labourers working in the informal economy. The purpose of this study is to fill this gap by evaluating the motives of child labourers, through three competing theorisations of the informal economy.